The willingness of community pharmacists in collaborative care of frail elderly in nursing homes - Mohd Faiz AL; Marhanis Salihah Omar (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
An increase in the number of residents in nursing homes has become a significant concern due to the rise in medication demand and subsequently medicationrelated issues, especially in frail elderly. Community pharmacists are the closest healthcare professionals available that can contribute to this population to allow optimal utilization of the prescribed drugs and to prevent drug-related problems. The present study aimed to investigate the awareness of community pharmacists on issues regarding frail elderly and to determine their willingness in collaborative care of frail elderly in nursing homes and the services they are willing to offer. This was a cross-sectional study utilising a set of questionnaire that was delivered to practicing community pharmacists in Peninsular Malaysia from June 2018 until December 2018. Majority of the participants agreed to the fact that aging is the primary cause of frailty (n=98, 88.3%), and that chronic disease is also a cause of frailty (n=96, 86.5%). Most of the community pharmacists were also keen to participate in the collaborative care of frail elderly, and were willing to provide their pharmacy service to the frail elderly. There was a positive correlation between the awareness of community pharmacists on issues regarding frail elderly and their willingness on collaborative care of frail elderly in nursing homes (r=0.374, n=111, p=0.01). Majority of the pharmacists were aware of the issues regarding the frail elderly, and were willing to participate in the collaborative care of frail elderly in nursing home.